The Influence of Job Happiness and Leadership Style on Lecturer Performance with Job Satisfaction as an Intervening Variable at Perintis Indonesia University - Andika, Afri; Rahmawati, Reni; Pawirosumarto, Suharno (Dinasti Publisher, 2026)
This study aims to analyze the influence of job happiness and leadership style on lecturer performance with job satisfaction as an intervening variable at Perintis Indonesia University. The research employed a quantitative explanatory design using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. A total of 100 lecturers were selected as respondents through purposive sampling. The results reveal that job happiness has a negative and significant effect on job satisfaction, but does not significantly affect lecturer performance, either directly or indirectly through job satisfaction. Leadership style, on the other hand, has a positive and significant effect on both job satisfaction and lecturer performance, indicating that effective leadership plays a crucial role in enhancing academic performance. Meanwhile, job satisfaction does not significantly influence lecturer performance, nor does it mediate the relationship between job happiness and lecturer performance or between leadership style and lecturer performance. These findings highlight that lecturer performance at Perintis Indonesia University is strongly shaped by leadership style rather than by job happiness or job satisfaction. The study contributes to organizational behavior literature by showing the central role of leadership in academic performance, while also emphasizing the limited role of job happiness and satisfaction in this context.